Pakistan : NWFP Growth Policy Note - World Bank (Washington, DC, 2014)
The Government of the North West Frontier Province requested, in the spring of 2007, an economic growth policy note as a follow up to the Provincial Economic Report of December 2005. The provincial government was in particular interested in analysis at the industry level of key industries with high growth potential, and a joint decision was quickly made to study the value chain of three industries; horticulture, furniture, and gems and jewelry. In addition to studying constraints to growth at the sector level, the intent has been to also have an in-depth analysis of the provincial investment climate in a chapter on crosscutting constraints. This would draw on data from the survey that would form the basis for the Second Investment Climate Assessment to be produced by the World Bank. The data from this survey has been delayed, so the crosscutting section of this policy note with the investment climate analysis will be presented in a follow up version of the policy note in the last quarter of 2008. Volume 1 is the main report, and Volume 2 consists of annexes.